CONSUMMATE LOVE VALUED BY STERNBERG’S TRIANGULAR OF LOVE REFLECTED IN “SUNRISE IN HEAVEN” (2019) MOVIE: PSYCHOLOGICAL APPROACH - Elhamsyah, Galuh Virginia; Rudianto, Gaguk (Universitas Putera Batam, 2024)
Abstract This study aims to explain and analyze the phenomenon of love proposed by an expert Robert J Sternberg to the main characters in the film Sunrise in Heaven (2019). This research is a type of qualitative descriptive research, and the data source taken is the film Sunrise in Heaven (2019). This film is based on Jan Hurst's true-story novel entitled